Cadmium sulphide thin films deposition and characterization for device applications. (2022) - Alam, A.; Kumar, S.; Singh, D.K.
Abstract: Thin films of metal chalcogenides (sulphides, selenides, and tellurides) are investigated, and group II-VI semiconducting materials are more attracted to the thin films, and researchers are more interested in group II-VI semiconducting materials because of their use in photovoltaic cells, photoconductors, optical filters, solar cells, sensors, and other optoelectronic devices. Cadmium sulphide is a semiconducting material that corresponds to the II-VI family and has an energy bandgap of 2.42 eV. It is significant because of their numerous applications in optoelectronic devices, solar cells, LEDs, photoconductors, and other fields. It's also beneficial for window layers in CdTe or CuInSe2-based high-efficiency thin-film solar cells. It can be prepared by several techniques like chemical bath deposition (CBD), electrodeposition, thermal evaporation, spray pyrolysis, molecular beam epitaxy, etc. We have prepared CdS thin films over Molybdenum substrate using a non-aqueous medium by the CBD method. The electrolyte was made by combining the AR grade of cadmium acetate (0.24 M) dissolved with ethylene glycol and ethanol (ratio = 1:2) and the electrolyte temperature was kept at 130 °C with 220 rpm. Molybdenum substrate was dipped into the electrolyte using rigid support and thiourea (0.35 M) was influenced by the prepared electrolyte. The film was deposited for 20 min, and the deposited films was found to be well adherent to the substrate and free of voids, pinholes, and pits. XRD, FESEM, EDS, AFM, and FTIR were used to see into the solid-state features of the films which have been deposited. The deposited film shows a significant peak at 2θ = 26.24 0 with the (0 0 2) plane, suggesting that the film has a crystalline hexagonal structure. Using AFM, RMS roughness value is equal to 92 nm. Compositional analysis peaks reveal the availability of Cd and S.